Efficient Recycling and Reuse of Waste Concrete on a Construction Site (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
During the construction of the high-speed rail from Wuzhong to Yinchuan in China, a huge amount of concrete wastes was generated. From the viewpoint of reducing the transportation cost, decreasing the consumption of natural resources and saving land space, it was decided to recycle and reuse of the concrete wastes in the construction work of the high-speed rail. This paper deals with the technical feasibility of reusing the concrete wastes taking into account the actual conditions on the construction site. The concrete wastes were crushed in a plant for producing natural coarse aggregates into recycled concrete aggregates (RCAs). Laboratory tests on the properties of the RCAs were carried out. It was found that that the physical and mechanical properties of the RCAs can meet the requirements in various standards. Then, experiments on the utilization of RCAs to manufacture concrete blocks for highway bank protection revetment were performed. The preliminary experimental results are found to be very encouraging.